Studying the Issue of Child Labor in the Oil Palm Plantation Sector - Alamanda, Asri Elies; Mangar, Irma; Damayanti, Miranda (Journal of Development Research, 2025)
A significant issue that many nations, including Indonesia, face is child labour, particularly in the oil palm plantation industry. A number of laws and policies, such as Law No. 13 of 2003 on Manpower, which specifically forbids the employment of child labour, and Law No. 23 of 2002 on Child Protection, have been put into place to safeguard children from exploitation. Furthermore, Indonesia is more committed to ending child labour and dangerous work because it has ratified international treaties including ILO treaties No. 138 and No. 182. Children's safety and sustainable community development are the two main goals of this research. This study's normative research approach focusses on examining laws and policies pertaining to child labour in Indonesia's oil palm plantation industry. Additionally, more and more palm oil companies are implementing sustainability strategies that address kid protection. Government and non-governmental organisation (NGO) programs emphasise access to education and public awareness of the risks associated with child labour. Violations of this rule can result in fines, business licence revocation, and criminal penalties.